Analisis Konsep Pelayanan Prima pada Layanan Paspor di Indonesia - Muhammad Faza Nugraha; Rahmawati Nurul Jannah; Habbi Firlana (Lembaga Pengembangan Kinerja Dosen, 2025)
Passport services are one form of strategic public service in the immigration administration system. This study aims to analyze the implementation of excellent service indicators in passport services in Indonesia, as well as to identify supporting factors, obstacles, and strategies that can be implemented to realize quality public services. This study uses a qualitative approach with a literature study method, reviewing various scientific sources and national policies in the 2015–2025 period. The results of the study indicate that the dimensions of action and ability of officers have been consistently implemented through service digitalization and increasing human resource capacity. However, the dimensions of attitude, attention, accountability, and appearance are not yet optimal in most immigration work units, especially in the 3T region. Supporting factors include HR professionalism, service innovation, and technology adoption, while inhibiting factors include bureaucratic cultural resistance, infrastructure inequality, and low digital literacy of the community. Strategic opportunities lie in accelerating digital transformation through SPBE, strengthening the capacity of the apparatus, community participation in service evaluation, and multi-party collaboration. Thus, realizing excellent passport services requires a transformative approach that integrates technological innovation, strengthening service culture, and governance that is adaptive to public needs.